The untapped potential of lineups: using eyewitness memory to rule out innocent suspects - Smith, Andrew M. (Psychology, crime & law, 2024)
Over the past 45 years, psychological scientists have invested a tremendous amount of effort into increasing the accuracy of suspect identifications from eyewitness lineup procedures. Those efforts have paid dividends, leading to the development of several practices that increase the accuracy of suspect identifications. Meanwhile, lineup rejections have largely been written off as lacking diagnostic value and little effort has been placed into understanding (1) why lineup rejections are less diagnostic than suspect identifications, and (2) how to increase the diagnostic value of lineup rejections. We show that preventing innocent-suspect identifications is not equivalent to demonstrating innocence and highlight several consequences of not being able to clear innocent suspects from police suspicion. We then review recent evidence, grounded in Signal Detection Theory, suggesting that lineup rejections are less diagnostic than suspect identifications because it is harder to reject a lineup of several faces than it is to identify a single face. When lineups are modified so that witnesses provide rejection ratings for each non-identified lineup member, rejection accuracy drastically increases. We highlight several questions for future research examining the potential for eyewitness memory to demonstrate innocence and question what impact suspect rejections might play in multiple-witness cases.